2012
DOI: 10.1172/jci60329
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic stress–induced activation of FoxO1 triggers diabetic cardiomyopathy in mice

Abstract: The leading cause of death in diabetic patients is cardiovascular disease; diabetic cardiomyopathy is typified by alterations in cardiac morphology and function, independent of hypertension or coronary disease. However, the molecular mechanism that links diabetes to cardiomyopathy is incompletely understood. Insulin resistance is a hallmark feature of diabetes, and the FoxO family of transcription factors, which regulate cell size, viability, and metabolism, are established targets of insulin and growth factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
286
2
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(311 citation statements)
references
References 59 publications
14
286
2
1
Order By: Relevance
“…Mice lacking Foxo1 in the heart displayed almost normal cardiac growth and function (Qi et al 2015), and Foxo1 inactivation partially rescued cardiac dysfunction and death in mice lacking cardiac IRS-1 and IRS-2 (Qi et al 2015), with similar results observed in db/db mice (Battiprolu et al 2012). In particular, we demonstrated the key role of Foxo1 in stimulating cardiac dysfunction by promoting β-myosin heavy chain (β-MHC) gene expression, a myocardial structural gene responsible for reduction in cardiac contractility (Qi et al 2015).…”
Section: :3supporting
confidence: 74%
See 1 more Smart Citation
“…Mice lacking Foxo1 in the heart displayed almost normal cardiac growth and function (Qi et al 2015), and Foxo1 inactivation partially rescued cardiac dysfunction and death in mice lacking cardiac IRS-1 and IRS-2 (Qi et al 2015), with similar results observed in db/db mice (Battiprolu et al 2012). In particular, we demonstrated the key role of Foxo1 in stimulating cardiac dysfunction by promoting β-myosin heavy chain (β-MHC) gene expression, a myocardial structural gene responsible for reduction in cardiac contractility (Qi et al 2015).…”
Section: :3supporting
confidence: 74%
“…Foxo1 serves as an important regulator in suppressing glucokinase gene expression, limiting glucose oxidation and utilization in the heart and increasing autophagy (Liu et al 2009, Battiprolu et al 2012, Qi et al 2013. Foxo1 stimulates cellular apoptosis by promoting gene expression of Bcl2 family members, such as Bim1 for caspase activation (Papanicolaou et al 2008).…”
Section: Cardiac Foxo1 Signalingmentioning
confidence: 99%
“…Phosphorylated FoxO1 can export from the nucleus and loses its transcriptional activity. Elevated cardiac FoxO1 levels may exert protective effects in some cardiomyopathies (25) but appear to be detrimental in diabetic hearts due to blunted cardiac insulin sensitivity and increased PDK4 gene expression (26). In the present study, we observed that neonatal DEX administration resulted in increased cardiac total FoxO1 and decreased p-FoxO1 protein content in 24-wk-old rats, indicating that elevated levels of activated FoxO1 may contribute to elevated levels of downstream PDK4 expression.…”
Section: Discussionsupporting
confidence: 56%
“…Despite the fundamental importance of metabolic plasticity in the heart, there is surprisingly little known about the transcriptional pathways that directly regulate myocardial substrate flux. When compared with the vast body of work that has defined gene-regulatory networks governing myocyte hypertrophy (14), the identification of transcription factors that are bona fide and direct regulators of myocardial nutrient flux is limited to a few members of the nuclear receptor superfamily (PPARs and ERRs) and the forkhead box factor FoxO1 (12,(15)(16)(17).…”
mentioning
confidence: 99%